Multi-Target Inhibitor CUDC-101 Impairs DNA Damage Repair and Enhances Radiation Response in Triple-Negative Breast Cell Line - Elsie Neo Seane; Shankari Nair; Charlot Vandevoorde; Alessandra Bisio; Anna Joubert (MDPI AG, 2024)
Background: Since the discovery that Histone deacetylase inhibitors (HDCAi) could enhance radiation response, a number of HDACi, mainly pan-HDAC inhibitors, have been studied either as monotherapy or in combination with X-ray irradiation or chemotherapeutic drugs in the management of breast cancer. However, studies on the combination of HDACi and proton radiation remain limited. CUDC-101 is a multitarget inhibitor of Histone deacetylases (HDACs), epidermal growth factor receptor (EGFR), and human epidermal growth factor receptor 2 (HER-2). In this paper, the effectiveness of CUDC-101 in enhancing radiation response to both proton and X-ray irradiation was studied. Methods: MCF-7, MDA-MB-231, and MCF-10A cell lines were pre-treated with CUDC-101 and exposed to 148 MeV protons, and X-rays were used as reference radiation. Colony survival, γ-H2AX foci, apoptosis, and cell cycle analysis assays were performed. Results: γ-H2AX foci assays showed increased sensitivity to CUDC-101 in the MDA-MB-231 cell line compared to the MCF-7 cell line. In both cell lines, induction of apoptosis was enhanced in CUDC-101 pre-treated cells compared to radiation (protons or X-rays) alone. Increased apoptosis was also noted in CUDC-101 pre-treated cells in the MCF-10A cell line. Cell cycle analysis showed increased G2/M arrest by CUDC-101 mono-treatment as well as combination of CUDC-101 and X-ray irradiation in the MDA-MB-231 cell line. Conclusions: CUDC-101 effectively enhances response to both proton and X-ray irradiation, in the triple-negative MDA-MB-231 cell line. This enhancement was most notable when CUDC-101 was combined with proton irradiation. This study highlights that CUDC-101 holds potential in the management of triple-negative breast cancer as monotherapy or in combination with protons or X-ray irradiation.